Molecular Characteristics of Burkholderia pseudomallei Collected From Humans in Hainan, China - Zhu, Xiong; Chen, Hai; Li, Sha; Wang, Li-cheng; Wu, Duo-rong; Wang, Xu-ming; Chen, Ru-shou; li, Zhen-jun; Liu, Zhi-guo (Frontiers in Microbiology, 2020)
Melioidosis is a common infectious disease in Southeast Asia and Northern Australia. In Hainan, several cases have been reported, but no systematic study has yet been done on the molecular epidemiology profiles of the organism. An investigation of the molecular epidemiology links and population structure of Burkholderia pseudomallei would help to better understand the clonally of the isolates and differences among them. In this study, multilocus variable-number tandem repeat analysis (MLVA), and multilocus sequence typing (MLST) were applied to examine the epidemiological relatedness and population structure of 166 B. pseudomallei isolates obtained during 2002–2014 in Hainan, China. Both the MLVA_4 and MLST approaches had high discriminatory power for this population, with diversity indices of 0.9899 and 0.9457, respectively. However, the MLVA_4 assay showed a higher discriminatory power than the MLST approach, and a variable-number tandem repeat (VNTR3 933) found by the MLVA approach was the most useful in discriminating strains from this province. A total of 166 strains yielded 99 MLVA_4 genotypes, of which 34 genotypes were shared by 101 isolates, for a clustering rate of 60.8% (101/166), which suggested that some cases may have a common source. Additionally, 65 isolates showed distinct genotypes, indicating that more than 39.2% (65/166) of melioidosis cases in Hainan had epidemiologically unrelated or sporadic characteristics. The 166 isolates were resolved into 48 STs, of which five STs (ST55, -70, -46, -50, and -58) were here found to be predominant. Phylogenetic analysis of 116 isolates conducted using the eBURST v3 segregated the 48 STs into eight groups with ST50 as predicted founder, and 21 STs were found to be singletons, which suggest that the strains in the Hainan region represent a high diversity of ST clones, indicating that many B. pseudomallei clone groups are endemic to this region. Moreover, ST50 had 5 SLV, 7 DLV, 6 TLV, and 29 satellite STs and formed a radial expansion pattern, suggesting that the melioidosis epidemic in this study was mainly caused by the clonal expansion of ST 50. Phylogenetic analysis on global scale suggests that China’s isolates are closely related to isolates from Southeast Asia, particularly from Thailand and Malaysia.